Spring 1994 field report, Hank Zaletel - Zaletel, Hanket al (1994)
An annotated list of birds sighted by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed